Vaccines: Advancements, Impact, and the Road Ahead in Medicine - Ahmad Jamal (BULLET : Jurnal Multidisiplin Ilmu, 2023)
The dynamic field of medicine is examined in this overview, with a focus on new developments, difficulties, and moral issues. It starts by breaking into the science behind vaccines, going over their types, development, and importance for public health. The effects of precision medicine, immunotherapy, gene editing, telemedicine, and nanotechnology on patient care, diagnosis, and treatment are examined. Immunotherapy uses the body's own defenses against diseases such as cancer, whereas precision medicine customizes therapies based on a patient's genetic profile. Telemedicine increases access to healthcare remotely, while gene editing may provide treatments for hereditary illnesses. Advanced imaging and targeted medicine delivery are made possible by nanotechnology.  Global health programs strive to achieve equitable healthcare for all people by addressing healthcare gaps, particularly in low-income regions.. A number of legal and ethical issues surface, especially in relation to telemedicine and AI diagnostic technologies, raising concerns about consent and accountability. The field of medicine is poised for revolutionary progress in the future, provided that obstacles such as data protection, regulatory compliance, workforce adaptation, and ethical issues are skillfully managed. Healthcare systems that navigate successfully maximize medical innovation to deliver exceptional patient care everywhere.